2012
DOI: 10.1002/pen.23358
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silver nanoparticles in electrospun polyacrylonitrile nanofibers using tea polyphenols as the reductant

Abstract: Uniformly dispersed Ag nanoparticles (AgNPs) with diameter about 5 nm embedded in electrospun polyacrylonitrile (PAN) nanofibers were synthesized by using tea polyphenols (TP) as the reductant. The reducing ability of TP toward Ag ions was characterized by Fourier transform infrared spectroscopy and ultraviolet–visible spectra, and the results revealed that TP exhibit satisfied reducing ability in the synthesis process. Transmission electron microscopy observation showed that the synthesized spherical AgNPs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…There are also a variety of particle fillers (Fig. d), like calcium carbonate , mica , glass beads , talc , silver , zinc oxide , titanium dioxide , and fly ash .…”
Section: Filler Reinforcementmentioning
confidence: 99%
“…There are also a variety of particle fillers (Fig. d), like calcium carbonate , mica , glass beads , talc , silver , zinc oxide , titanium dioxide , and fly ash .…”
Section: Filler Reinforcementmentioning
confidence: 99%
“…In contrast to previously mentioned antibiotics, silver source is indirectly introduced in the polymer solution in the form of a salt. This mainly includes AgNO 3 , but also AgZ and AgCl . For this, resultant materials would need to be subjected to a later reduction process to activate and produce AgNPs.…”
Section: Biocide Electrospun Nanofibersmentioning
confidence: 99%
“…Similar biocide performance was observed by Rujitanaroj et al against gram‐positive Staphylococcus aureus and Gram‐negative Escherichia coli bacteria, by combining DMF with UV irradiation in electrospun PAN nanofibers. In the study of Zou et al , uniformly dispersed AgNPs with mean diameters of about 5 nm embedded in electrospun PAN nanofibers were synthesized by using tea polyphenols. Results suggested that PAN polymer and polyphenols both served as stabilizer during the synthesis of AgNPs because of the chelating interactions of Ag with cyano groups and phenolic hydroxyls.…”
Section: Biocide Electrospun Nanofibersmentioning
confidence: 99%
“…Polymer modification techniques could be introduced to improve the properties of AN-based copolymers. The active C≡N groups presented in acrylonitrile copolymers strongly adsorb silver and promote the interaction with silver through the chelating effect [33].…”
Section: Introductionmentioning
confidence: 99%